What makes Napa Napa? The roots of success in the wine industry - Anil Hira; Tim Swartz (Wine Economics and Policy, 2014)
California is world-renowned for the ability to produce world class quality wine. At the center of this achievement is the development of Napa as a premier wine producing region. We examine the sources of Napa's success by testing factors from leading industrial location theories against statistical and qualitative evidence. Using an unusual database of county-wide data on the wine industry to compare Napa's success with other wine-producing regions of California, we can control for different historical factors and economic conditions that temper most comparative wine studies. Many regions in California can produce world class wine, but none enjoy the same level of returns as Napa. Path dependency and distance to markets are poor explanations for the relative success of wine regions. We find that while terroir, or natural comparative advantage, has some evidence behind it, social capital and entrepreneurship behind technological leadership are central to Napa's competitive advantage.
Keywords: 330; California; Economic development; Entrepreneurship; Industrial location; Napa; Regional economics; Social capital; Wine industry; Terroir